2019
DOI: 10.4025/actascianimsci.v41i1.44425
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and structural characteristics of <i>Urochloa decumbens</i> Stapf. deferred pasture grazed by heifers under two periods of protein-energy supplementation

Abstract: The aim of this study was to evaluate the morphological and structural characteristics of deferred Urochloa decumbens Stapf. ‘Basilisk’ grazed by Nellore heifers under two periods of protein and energy supplementation (PES). The experiment was carried out from Jun 21 to Nov 15, 2016, under a completely randomized design and two PES periods (55 [P55] and 147 [P147] days). Forage mass (FM), leaf blade dry mass (LBDM), stem dry mass (SDM), dead material dry mass (DMDM), canopy height (CH), and forage bulk density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
1
2
0
1
Order By: Relevance
“…It is important to highlight that up to 33 days of fallowing, the final weight was not altered, most likely due to the high forage supply that exceeded the minimum of 3.5 times the necessary (33) , allowing the animals to express all their ability to select species more palatable and of better nutritional value (34) . Results similar to those observed in the study were reported by Santos et al (28) , who evaluated the effect of supplementation in Santa Inês lambs finished on native pasture, and found a final body weight of 23.63 kg in animals receiving 1% supplementation, and by Silva et al (29) , who studied Urochloa decumbens and reported a forage reduction in the dry season, with seasonality in animal production and animal weight in the last evaluation period. Santos et al (7) argued that the fallowing leads to the accumulation of mature stems and dead material and a decrease in the availability of leaves, with a consequent reduction in animal consumption and performance.…”
Section: Resultssupporting
confidence: 89%
“…It is important to highlight that up to 33 days of fallowing, the final weight was not altered, most likely due to the high forage supply that exceeded the minimum of 3.5 times the necessary (33) , allowing the animals to express all their ability to select species more palatable and of better nutritional value (34) . Results similar to those observed in the study were reported by Santos et al (28) , who evaluated the effect of supplementation in Santa Inês lambs finished on native pasture, and found a final body weight of 23.63 kg in animals receiving 1% supplementation, and by Silva et al (29) , who studied Urochloa decumbens and reported a forage reduction in the dry season, with seasonality in animal production and animal weight in the last evaluation period. Santos et al (7) argued that the fallowing leads to the accumulation of mature stems and dead material and a decrease in the availability of leaves, with a consequent reduction in animal consumption and performance.…”
Section: Resultssupporting
confidence: 89%
“…There was no significant effect on CP content, which on average were lower than the critical level of the basal ruminant diet (Silva et al, 2019). Importantly, these results reflect the CP levels of elephant grass before ensiling (Table 1).…”
Section: Resultsmentioning
confidence: 66%
“…The lack of this technique becomes a limiting factor, stagnating this index at 0.80. Stockpiling is efficient to mitigate the seasonality effect of forage production and is technically efficient when considering the regrowth period and the grazing intensity of forage species (Silva et al, 2019).…”
Section: Discussionmentioning
confidence: 99%